Sudden sensorineural hearing loss after Covid-19 infection - Deewani, Muhammad Hammad; Siddiqui, Moghira Iqbal (Journal of the Pakistan Medical Association, 2023)
Covid-19 pandemic has taken the world by a storm, pushing the boundaries of human endurance and intellect. Caught at the horns of dilemma, humanity is still struggling with the management of the established symptoms not to mention the novel symptoms. In this regard, the novel symptoms must be highlighted to ensure proper and timely management. Viral aetiology has been an established entity for neurological deficits; hence, it would not be a huge leap to consider the correlation between Covid-19 and Sensorineural hearing loss (SNHL). Here, a case is being presented where the patient developed sudden sensorineural hearing loss after Covid-19 infection. Keywords: Hearing loss, Sensorineural, Pandemic, Sudden hearing loss.